Management and Standards of Madrasah Libraries - Setyaningsih, Rini; Irawati, Irawati; Al Ghifari, Mahdini; Sari, Arrum Intan (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2024)
As a center of information and a of knowledge, the madrasah library has an significant role in helping students develop their horizons. The purpose of this study is to ubderstand and know the management and standards of the madrasah library at MAN I Pekanbaru. The method used in collecting data in this study is through observation, interviews, and documentation. This atudy describes library organization, library work procedures, library work relations, collection and classification of library materials, cataloging, library user services, forming a reading culture, and madrasah library standards. MAN 1 Pekanbaru library has an organizational structure that is bound by good working relationships with internal stakeholders. Management of collections of library materials is carried out with directed planning, while user services, which include circulation, administration, reference, and digital services provide easy access. The classification (DDC) with e-DDC application support and cataloging using the Anglo American Cataloging Rules (AACR) system.